Impact of social networking sites on academic writing among Chinese postgraduates / Ma Jing Wei - Ma, Jing Wei (2016)

(untitled)
The development and proliferation of web 2.0 technologies as well as Social Networking Sites (SNSs) have expanded tremendously now that Social Networking is part of everyone‘s life. With the expansion of SNSs, scholars assume that this new platform plays an important role in academic writing. On the other hand, many Chinese EFL learners over a decade failed to improve their English academic writing due to the ineffective classroom teacher centred models (Rao and Chan, 2010). The aims of this study are to investigate the relationship between frequency of Chinese postgraduates using SNSs and English academic writing in terms of lexical complexity and to investigate the perception of the Chinese postgraduates on how SNSs usage affect their writing. This study uses two theoretical frameworks, the first one being the Typology of SNSs users which according to Brandtzæg and Heim (2011), SNSs users are classified as people who diversified behaviour into meaningful categories active SNSs users and inactive SNSs users, and second, the Lexical Richness Measurements which use the lexical variance (LV) and lexical sophistication (LS) formulas introduced by Laufer and Nation (1995). This study uses a mixed research method of both quantitative and qualitative approaches. For the quantitative part of the research, a questionnaire was distributed to 61 Chinese postgraduates in University of Malaya. The written text of these 61 students were also collected after they answered the questionnaire. The active and inactive SNSs users were identified and three students from each group were randomly selected and iv interviewed. The results of the questionnaire and written text findings indicated that there were no significant relationship between frequency of participation logging in SNSs and their academic writing in terms of lexical complexity. However the results of the interviews revealed that the inactive SNSs users had better agreement of vocabulary acquirement, attitude and motivation towards academic writing compared to the active SNSs users (the usage of SNSs in terms of the high participation of users are called active SNSs users).